A new clade of insect-specific flaviviruses from Australian Anopheles mosquitoes displays species-specific host restriction. - Colmant, AMG; Hobson-Peters, J; Bielefeldt-Ohmann, H; van den Hurk, AF; Hall-Mendelin, S; Chow, WK; Johansen, CA; Fros, JJ; Simmonds, P; Watterson, D; Cazier, C; Etebari, K; et al. (American Society for Microbiology, 2017)
Flaviviruses are arthropod-borne viruses found worldwide and are responsible for significant human and veterinary diseases, including dengue, Zika, and West Nile fever. Some flaviviruses are insect specific and replicate only in mosquitoes. We report a genetically divergent group of insect-specific flaviviruses from Anopheles mosquitoes that do not replicate in arthropod cell lines or heterologous Anopheles species, exhibiting unprecedented specialization for their host species. Determination of the complete sequences of the RNA genomes of three of these viruses, Karumba virus (KRBV), Haslams Creek virus, and Mac Peak virus (McPV), that are found in high prevalence in some Anopheles mosquito populations and detection of virus-specific proteins, replicative double-stranded RNA, and small interfering RNA responses in the host mosquito species provided strong evidence of a functional replicating virus in the mosquito midgut. Analysis of nucleotide composition in the KRBV and McPV sequences also revealed a pattern consistent with the virus evolving to replicate only in insects. These findings represent a significant advance in our knowledge of mosquito-borne flavivirus ecology, host restriction, and evolution.